FABLE Scenathon database 2023 - Douzal, Clara; Chemarin, Charlotte; Mosnier, Aline; Orduña-Cabrera, Fernando; Jones, Sarah; Adenäuer, Lucie; Vittis, Yiorgos; Cozza, Davide; Diaz, Maria; Javalera Rincón, Valeria; Rios, Alejandro; Sandoval, Marcial; et al. (Zenodo, 2024)
This database contains key parameters and variables from the 2023 Scenathon which has been run by the Food, Agriculture, Biodiversity, Land-Use, and Energy (FABLE) Consortium. A scenathon - a scenario marathon - is a multi-objective challenge that allows a decentralized global modelling approach with multiple models developed by different teams in the world at national and regional scales, and a methodology to link them ensuring international trade consistency and tracking collective progress towards the achievement of global sustainability targets.